A comparative ultrastructural study of spermatozoa of the teiid lizards Cnemidophorus gularis gularis, Cnemidophorus ocellifer, and Kentropyx altamazonica (Reptilia, Squamata, Teiidae) - Teixeira, Ruscaia Dias (2016)
The ultrastructure of the spermatozoa of Cnemidophorus gularis gularis, Cnemidophorus ocellifer, and Kentropyx altamazonica is described for the first time. Mature spermatozoa of Cnemidophorus spp. and K. altamazonica differ in the occurrence of a perforatorial base plate, the enlargement of axonemal fibers 3 and 8, and shape of mitochondria. The comparisons of the ultrastructure sperm of Cnemidophorus spp. and K.altamazonica with Ameivaameiva [J. Morphol. (2002) in press] suggest that Ameiva and Cnemidophorus are more similar to each other than either is to Kentropyx. Statistical analyses reveal that sperm of all three species studied are significantly different in the following dimensions: head, acrosome, distal centriole length, and nuclear shoulders width. There was no variable statistically different between the Cnemidophorus spp. only. The length of the tail, midpiece, entire sperm, and nuclear rostrum are significantly different between K. altamazonica and Cnemidophorus spp. Our results indicate that sperm ultrastructure presents intra and intergeneric variability.